KOMUNIKASI DUA ARAH SEBAGAI INTERAKSI EDUKATIF DALAM KISAH NABI ĀDAM ALAIHI AL-SALAM (AS) - Ahmad Yunus Mokoginta Harahap; Suwarno Suwarno (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2023)
Communication is a way to convey messages from one person to another. In the context of education, the teaching and learning process is a communication pattern that occurs between teachers and students or students. Education had happened since the beginning of human civilization, even before the first human, the prophet Ādam AS, was created to be a caliph on earth, narrated in the Al-Qur’ān Surah al-Baqarah verse 20. In this verse, there is an educational interaction between Allah SWT and the Angels. The purpose of this study was to determine the two-way communication pattern of educative interaction in the story of the prophet Ādam AS. This study uses a library research method. The data source comes from the verses of the Al-Qur’ān and Hadith as the primary data source and the opinions of the scholars in the turhat book as a secondary data source. Data analysis uses the content or content analysis, which is then described in depth. The results of this study found a two-way communication pattern as an educative interaction in the story of the prophet dam as between Allah SWT and angels. In this communication, Allah SWT provides learning or educative interactions to the Angels regarding their erroneous perception that the Khalifah fī al-arḍ (Ādam AS and his descendants) will do damage and like to kill each other on earth. This perception is then changed by Allah SWT with strategies and methods of throwing discourse (feedback).